Особенности адекватного математического моделирования динамического поведения роторов в активных магнитных подшипниках газотранспортных и газотурбинных установок - Мартыненко, Г. Ю. (Eastern-European Journal of Enterprise Technologies, 2009)
Problems of adequate mathematical models construction for rigid rotors of gas-transport and gas-turbines plants with the active radial and axial magnetic bearings with different power characteristics are considered. The offered analytical models can be put in the basis of simulations models which are intended for calculations of the dynamic stability for the different operations modes of rotors machines